Using Artificial Intelligence to Predict Financial and Administrative Risks: An Applied Study on Development International Bank for Investment and Funding for the Period 2015–2024 - Mohammed Muneam Ali; Yasir Majeed Dahdooh; Layth Abdul Hamza Ghazzay (International Journal on Economics, Finance and Sustainable Development, 2026)
Research aims to set effect Use Technologies intelligence artificial in Prediction At risk Finance And administrative, That's from during study Applied on bank Development International For investment and financing For the period Extended From 2015 to 2024. Launching Search from The need Increasing I have Institutions Banking to development tools analytical more capacity on Dealing with Complexity growing in Data, and strengthening accuracy Decisions Private Management Risks, no Sima in shadow Changes Economic Finance that I witnessed it market Iraqi during years The latter. And it has I depend Search Methodology In practice built on analysis Data Historical For the bank, Design Models predictive Using Technologies intelligence artificial, like Models forests randomness and XGBoost and networks Nervousness, With the aim comparison Her ability on Prediction At risk In exchange Methods traditional Approved in administration The risks. Also Eat Search group from Variables Finance And administrative, like Indicators stumbling Credit, levels Liquidity, adequacy head the money, Indicators Compliance And governance, and rotation Employees, and extent Its reflection on level Exposure For risks in The bank and it arrived. Search to that Use intelligence artificial maybe that Enhances accurately greater ability on Discovery early on Risks, And reduces from levels non certainty when Taking Decisions, Please on His contribution in to improve efficiency Allocation Resources and strengthening quality Governance Interior. As well. an offer Search group Recommendations practical To promote to merge Models smart in system administration Risks, Guarantee Sustainability Her performance from during Review Periodic and governance Models.